(untitled) (Bangladesh Journal of Medical Science, 2011)
Background & objective: Stroke is a dreadful health hazard all over the world as well as in our country and one of the leading causes of mortality & morbidity. The relationship between serum C-reactive protein (CRP) level and post stroke outcome is not well studied especially in Bangladesh. We were interested to study this relationship in our country. Materials & methods: A cross sectional prospective study was performed on 50-stroke patients. Serum CRP & Lipid profile was determined. Post stroke outcome was measured by modified ranking scale (good outcome, score within 0 – 2 & bad outcome, score within 3 – 6). The subjects were divided in two groups, CRP level above or below 10 mg/L. Statistical analysis was performed by using SPSS software. Chi-square test & Spearman’s rho correlation test was done to see the level of significance. Results: Mean serum CRP level was 9.69 mg/L that was higher than normal subjects. Correlation analysis between serums CRP level of stroke patients with post stroke outcome was found to be positively correlated (r = 0.598/p<0.01). Conclusion: Serum CRP level may be used as a prognostic marker in stroke patients and it helps to make necessary management plan to physician. DOI: 10.3329/bjms.v10i1.7316 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.29-33